P767 Quantum Blue® infliximab POC user performance evaluation. (16th January 2018) - Fellay, B; Kopertowska-Majchrzak, M; Burri, E; Ueberschlag, M -E; Ritz, A; Schuster, T
Abstract: Background: The objective of the user performance evaluation was to demonstrate the ease-of-use of the Quantum Blue ® Infliximab POC system, consisting of the Quantum Blue ® Infliximab test and the Dilution Set, to allow non-laboratory professionals to independently and correctly determine infliximab concentration starting from an existing patients' serum samples within 15 min under actual conditions of use and without further equipment. Methods: The ability of point-of-care users to obtain correct results was evaluated by testing result agreement between users' Quantum Blue ® Infliximab measurements from two lots and laboratory reference values (RIDASCREEN IFX MONITORING ELISA (r-biopharm) for a set of 40 clinical serum samples. To demonstrate the ease-of-use of the test for non-laboratory professionals, the performance of the users was compared with that of laboratory personnel at BÜHLMANN who performed the same measurements with the Quantum Blue ® POC system. Test robustness, ease and comfort of use as well as the clearness of the given instructions was further assessed in a questionnaire. Three point-of-care-sites, in three geographically distinct locations participated in this study. Operators were non-laboratory medical personnel such as nurses, medical practice assistants or physicians. Two operators were recruited per site. Sites: (1) Hôpital Cantonal Fribourg, Fribourg, Switzerland, (2) Wielospecjalistyczny Szpital Wojewódzki, Gorzów Wlkp, Poland, and (3) Kantonsspital Baselland, Liestal, Switzerland. Results: None of the six non-laboratory professionals of the three POC sites, received a false-positive or false-negative result, based on an optimal therapeutic window of 3 to 7 µg/ml (Vande Casteele et al., 2015). Overall, non-laboratory professionals at the POC sites received comparable results than laboratory professionals at BÜHLMANN. Bias at 3 and 7 µg/ml, clinical decision points for therapeutic drug monitoring, when compared with laboratory reference values, were determined to 4.8 % and 7.4 % (site 1), 2.4 % and 5.8 % (site 2) as well as to 12.9 % and 17.0 % (site 3). The total agreement of non-laboratory professionals' results with reference infliximab values was 82.3 % (site 1), 80.8 % (site 2) and 83.8 % (site 3). Overall the non-laboratory professionals' assessment of the POC assay in terms of the robustness, ease and comfort of use was very positive. Conclusions: The outcome of this study suggests that the Quantum Blue ® Infliximab POC System, which determines infliximab levels in serum specimen, is easy-to-use, the given instructions are comprehensive, and results are comparable and interchangeable between different POC sites and laboratories.